Chemopreventive effect of punica granatum on human lung carcinoma A549 cells - Abdul Ghani, Radiah; Nik Abdul Malek, Nik Nurasyikin (2014)
Lung cancer is the most common type of cancer which the mortality rate increases year by year. Therapeutic drug could not control the progression of cancer effectively as it is contributing to the side effects. An alternative strategy such as chemoprevention using natural product should be investigated. P. granatum is one of the prophetic foods which has a potential to be a chemopreventive agent. Polyamine plays an important role in the proliferation phase and the viability of the cells. In cancer cells, the intracellular polyamine present in increased concentration. The polyamine metabolism in cancer cells shows a good potential site for chemoprevention. This study is aimed to evaluate the chemopreventive effect of the pomegranate on the growth of human lung carcinoma A594 cells. The cytotoxicity test had been conducted by using MTT assay while the effect of pomegranate juice on A549 cancer cells growth were evaluated by trypan blue exclusion assay. The protein and polyamine content were quantified using Lowry assay and HPLC, respectively. The result showed that various concentrations of pomegranate juice treatment range from 0.0 to 3.0% had resulted a dose dependent inhibition of A549 cell growth. The inhibitory concentration, IC50 value, at which 50% inhibition of cell growth was observed, was 0.8% after 48hr exposure and 1.5% after 72hr and 96hr exposure. At the concentration of 1%, inhibition of growth was observed by showing decreased in cell number and protein content. From the results, the protein content of A549 cells treated with 1% of the pomegranate juice was lower compared to the untreated A549 cells. At 96 hour, total polyamine content was lower compared to the controls. This preliminary study shown that, the pomegranate juice could inhibit the proliferation of A549 cancer cells. Hence, it could be a good strategy to prevent or slow the growth of cells.